Socket shield technique and delayed implant placement in maxilla: a series of five case reports - Rola Muhammed Shadid (BMC, 2022)
Abstract Background Tooth extraction is often followed by remodeling of hard and soft tissues, while socket shield technique has been proposed to prevent or minimize this remodeling. Socket shield accompanied with delayed implant placement is a novel technique that could be used when delayed implantation is selected; however, more scientific based evidence is required to recommend this technique as everyday clinical practice. Thus, the aim of this case series was to assess the clinical, radiographic, and esthetic outcomes of the delayed placed implants associated with previously prepared socket shield at 3-15 months follow-up after loading. The stability of the shield and the depth of soft tissue penetration palatal to the shield at reentry of 3-6 months were also assessed. Cases presentation Five case reports of socket shield with delayed implant placement were described in the study. The facial shields were prepared and simultaneously the sockets were grafted with mineralized allograft particles, then the implants were placed 3-6 months later. Periodontal probe was used to measure the depth of soft tissue penetration palatal to the shield at reentry. Clinical indices of bleeding index, plaque index, and probing depths were recorded. Radiographic evaluation to record the amount of marginal bone loss post-loading, esthetic assessment using modified pink esthetic score, and patient assessed outcomes were also evaluated at 3-15 months follow-up after loading. At 3-6 months reentry, all shields were stable with maintenance of the facial bone and with extreme hard tissue formation in the sockets. All five implants were successful and functional without any pain or inflammation, with optimal soft tissue health and esthetics, and with minimal radiographic marginal bone loss at the last follow-up visit (3-15 months after loading). Conclusions Within the limits of this study, socket shield technique with delayed implant placement could be a predictable minimally invasive option for cases requiring delayed implant placement; however, a long-term well-designed clinical proof is warranted.